The Use of Music as a Stress Coping Mechanism among Generation Z in Bogor City - Maulina Dwi Handayani; Hudi Santoso; Enden Darjatul Ulya; Rici Tri Harpin Pranata (Peneliti.net, 2026)
This research was motivated by the increasing psychological pressure experienced by Generation Z, who grew up in an era of rapid technological development, which made effective coping strategies essential for managing stress. Music was one of the most widely used coping media because it was considered capable of providing distraction, emotional relief, and a channel for self-expression. The main problem explored in this study was how the use of music as a coping mechanism influenced stress levels among Generation Z in Bogor City. The purpose of this research was to analyze the extent to which music contributed to helping adolescents and young adults manage the stress they faced. A quantitative method was employed using a survey technique, involving 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression. The findings showed that music had a significant effect on coping ability, with a significance value below 0.05 and a coefficient of determination (R²) of 0.755, indicating that 75.5% of coping ability was explained by music use. The study concluded that music played an important role as a coping medium that helped Generation Z regulate emotions, calm their minds, and reduce psychological pressure. It was recommended that educational efforts on healthy coping strategies be further developed and that the use of music as a supportive mental health tool be promoted more intentionally among Generation Z.